2020
DOI: 10.3389/fneur.2020.00062
|View full text |Cite
|
Sign up to set email alerts
|

Increased CSF Soluble TREM2 Concentration in Patients With Neurosyphilis

Abstract: Objective: To explore cerebrospinal fluid (CSF) levels of soluble triggering receptor expressed on myeloid cells 2 (sTREM2) and neurofilament light proteins (NFL) in patients with neurosyphilis (NS). Methods: We enrolled 71 NS patients (41 early-NS and 30 late-NS patients) and 20 syphilis but non-NS patients whose CSF samples were collected. The CSF levels of the microglial activation biomarker sTREM2 and neuronal injury biomarker NFL were measured using ELISA. Results: CSF sTREM2 levels were significantly hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Triggering receptor expressed on myeloid cells 2 (TREM2), which is mainly expressed by microglia, the resident immunocytes in central nervous system (CNS), have been extensively studied and found associated with microglia functions [ 1 ]. Evidence from observational studies indicates that the levels of soluble TREM2 (the secreted ectodomain of TREM2, sTREM2) were higher in cerebrospinal fluid (CSF) of patients with CNS disorders of different causes, including inflammatory [ 2 4 ], neurodegenerative [ 5 11 ], and vascular diseases [ 12 , 13 ]. However, given careful study design of observational analyses, whether CSF sTREM2 levels account for the observed development of these neurological disorders remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Triggering receptor expressed on myeloid cells 2 (TREM2), which is mainly expressed by microglia, the resident immunocytes in central nervous system (CNS), have been extensively studied and found associated with microglia functions [ 1 ]. Evidence from observational studies indicates that the levels of soluble TREM2 (the secreted ectodomain of TREM2, sTREM2) were higher in cerebrospinal fluid (CSF) of patients with CNS disorders of different causes, including inflammatory [ 2 4 ], neurodegenerative [ 5 11 ], and vascular diseases [ 12 , 13 ]. However, given careful study design of observational analyses, whether CSF sTREM2 levels account for the observed development of these neurological disorders remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…By comparing the effects of natalizumab and mitoxantrone, only CSF sTRME2 has shown the potential utility as a biomarker for MS treatment effects ( 12 ). In addition, the level of CSF sTREM2 was increased in patients with neurosyphilis (NS), and peaked at the late stage, compared with the control groups ( 23 ).…”
Section: Discussionmentioning
confidence: 97%
“…Because current tests lack sensitivity, new research has been exploring novel CSF biomarkers and their potential to aid in the diagnosis or exclusion of NS. For instance, myeloid and microglial activation markers such as MIF (Macrophage migration inhibitory factor) and sTREM2 (soluble Triggering receptor expressed on myeloid cells 2) have been reported to be differentially expressed in the CSF of patients with NS and have emerged as promising tools for establishing a diagnosis, particularly in the setting where non-treponemal tests are negative but there is high clinical suspicion [ 36 , 37 ]. Furthermore, Zhang et al reported that several CSF proteins such as neurogranin, BACE1, and Tau are increased in patients with Alzheimer’s Disease in comparison to those with NS, which may be useful in the setting of patients with cognitive decline and a past history of syphilis [ 38 ].…”
Section: Discussionmentioning
confidence: 99%